Subjectivity of artificial intelligence in criminal law: New challenges - Hammouri, Jafar Ali Ahmad (Edelweiss Applied Science and Technology, 2024)
The article aims to evaluate which changes in criminal law can influence the improvement of defining the legal personality of artificial intelligence. To achieve this, the object of study is AI-based technologies that could become subjects of criminal law. The scientific objective of the article is to identify and organize the most necessary changes in Jordan's criminal legislation to establish the legal personality of artificial intelligence. The research methodology involves applying a consolidated ranking of the proposed changes in criminal law. As a result, a list of proposed amendments to Jordan's criminal legislation is presented, which enhances the definition of artificial intelligence as a legal subject. A model for organizing these changes from the most significant and necessary today to the less influential is also presented. Prospects for further research should involve a deeper assessment of the moral and ethical issues of artificial intelligence and the regulation of its activities.